Добрыня Никитич и Алеша Попович: русские былины и сказки / [ред. А. В. Чубрикова ; оформл. К. Гурева] - Чубрикова А. В. (Вагриус, 2004)
Экземпляры: (20181102) / Инвентарный номер: 40814 / Цена: 69.52 / Сис.шифр: Ш3(2=1Р) / Авт.знак: Д 573 / ГРНТИ: 17.71.91 / ББК: Ш3(2=1Р)-611